2010
DOI: 10.2754/avb201079s9s013
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Egg Yolk Colour in Different Systems of Rearing Laying Hens

Abstract: A total of 72 laying hens (ISA BROWN hybrid combination) were divided into two groups. Thirty-six layers in the first group were reared on litter while the second group of layers was reared using the cage rearing system. Samples of eggs were collected from both groups for a period of seven months. Yolk colour was determined using a portable spectrophotometer using a newly developed method, which complied with the CIELAB system. Yolk colour indicator L* decreased for the rearing system on litter, i.e. egg yolk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…The colour values recorded in the present work were consistent with the ranges reported for chicken yolks by Kljak et al (2012) and the a* values reported by Dvořák et al (2010), but notably higher than the results of Aygün and Olgun (2019) for chicken and quail yolks. In the study conducted by Aygün and Olgun (2019), birds were strictly housed in cages, and fed daily rations of 17 -20% HP with no additional carotenoid supplementation noted.…”
Section: Coloursupporting
confidence: 92%
“…The colour values recorded in the present work were consistent with the ranges reported for chicken yolks by Kljak et al (2012) and the a* values reported by Dvořák et al (2010), but notably higher than the results of Aygün and Olgun (2019) for chicken and quail yolks. In the study conducted by Aygün and Olgun (2019), birds were strictly housed in cages, and fed daily rations of 17 -20% HP with no additional carotenoid supplementation noted.…”
Section: Coloursupporting
confidence: 92%
“…RCF values varied in a range of 12.9-13.3. 9 Our previous study 15 demonstrated a positive effect of litterbased rearing on egg colour parameters, as compared to cagebased rearing. During the 7-month monitoring, the parameter b * increased from the third month.…”
Section: Discussionmentioning
confidence: 99%
“…Redness and yellowness of mayonnaise were mainly attributed to the color of egg yolk. Dvořák et al (2010) reported that a* and b* values of egg yolk were around 5–11 and 33–43, respectively. On the other hand, a* and b* values of Asian sea bass fishbone bio‐calcium were 0.14 and 5.63, respectively (Wijayanti, Benjakul, & Sookchoo, 2021).…”
Section: Resultsmentioning
confidence: 99%